Effect of slope shape on soil aggregate stability of slope farmland in black soil region - Wang, Yuxian; Xu, Yingying; Yang, Huiying; Shen, Huibo; Zhao, Lei; Zhu, Baoguo; Wang, Jiangxu; Guo, Lifeng (Frontiers in Environmental Science, 2023)
The black soil area in Northeast China is the only agricultural production area in China that is still degraded and aggravated, and it is currently showing a continuous deterioration of development trends. If black soil resources are not protected in time, it will directly damage cultivated land and threaten national food security. Therefore, it is urgent to control soil erosion and protect black soil resources to reveal the occurrence and development of soil erosion under the interaction of various external forces on slopes in black soil areas and to clarify the influence of black soil structure characteristics on slope erosion processes. Straight slope, concave, and concave-straight compound slope farmland with a slope length of 1020 m were selected in Keshan Farm. The LB method was used to distinguish the breakage mechanism of black soil aggregates under different conditions (rainstorm, light rain, disturbance) and to quantitatively analyze the characteristics of soil aggregate stability changes and its influencing factors under different plow layers. In order to provide data support for the precise deployment of water conservation measures and the realization of soil nutrient management in this area.